A Methoxyamine‐Protecting Group for Organic Radical Battery Materials—An Alternative Approach. Issue 9 (15th April 2020) - Hansen, Kai‐Anders; Chambers, Lewis C.; Eing, Matthias; Barner‐Kowollik, Christopher; Fairfull‐Smith, Kathryn E.; Blinco, James P.
Abstract: An alternative synthetic route towards the widely employed electroactive poly(TEMPO methacrylate) (PTMA) via a thermally robust methoxyamine‐protecting group is demonstrated herein. Protection of the radical moiety of hydroxy‐TEMPO with a methyl functionality and subsequent esterification with methacrylic anhydride allows the high‐yielding formation of the novel monomer methyl‐TEMPO methacrylate (MTMA). The polymerization of MTMA to poly(MTMA) (PMTMA) is investigated via free radical polymerization and reversible addition–fragmentation chain‐transfer polymerization (RAFT), a reversible‐deactivation radical polymerization technique. Cleavage of the temperature‐stable methoxyamine functionality by oxidative treatment of PMTMA with meta ‐chloroperbenzoic acid ( m CPBA) releases the electroactive PTMA. The redox activity of PTMA was confirmed by cyclic voltammetry in lithium‐ion coin cells. Abstract : Radical move: Protect ! An alternative synthetic route towards the widely employed electroactive poly(TEMPO methacrylate) (PTMA) is demonstrated. Protection of the radical moiety of hydroxy‐TEMPO with a methyl functionality and subsequent esterification with methacrylic anhydride allows the high‐yielding formation of the novel monomer methyl‐TEMPO methacrylate (MTMA). Cleavage of the temperature‐stable methoxyamine functionality by oxidative treatment of PMTMA with meta ‐chloroperbenzoic acid gives the desired PTMA.